Effect of Ferrous Gluconate and Calcium Lactate Combined with Vacuum Osmotic Dehydration on Mass Transfer - ยืนยงพุทธกาล วิชมณี; โรจนเกียรติถาวร ณัฎฐิกา; ใหม่ยศ นันทมน (KKU Science Journal, 2015)
Osmotic dehydration is a pre-treatment method used prior to drying for partially removal of water from fruit and vegetable. It also results in enriched the physiologically active compound inflow from the osmotic solution into fruit and vegetable pieces. The influence of factor variations in ferrous gluconate concentration, calcium lactate concentration and vacuum impregnation treatment for osmotic dehydration of guava were studied. It was found that all three factors influenced osmosed guava firmness (p≤0.05). Interaction of ferrous gluconate concentration and vacuum impregnation treatment had an effect on iron content of osmosed guava (p≤0.05). Similarly trend was observed that both calcium lactate concentration and vacuum impregnation treatment together influenced calcium content of osmosed guava (p≤0.05). Each main factor of ferrous gluconate concentration, calcium lactate concentration and vacuum impregnation treatment affected content of water loss, solid gain and weight reduction (p≤0.05). The addition of high concentration of ferrous gluconate and calcium lactate (2%) resulted the osmosed guava had the highest iron and calcium content as 26.57 and 60.13 mg/100 g, respectively.